Exploring the Significance of Literary Texts to Enhance Intercultural Communicative Competence in Moroccan EFL Classrooms - Ousiali, Lahcen; Housni, Hamid; Amezoirou, Redouane (International Journal of Linguistics and Translation Studies, 2023)
Language teaching aims not only at enabling learners to communicate fluently and accurately through mastering pure linguistic skills; but also at training them to interact effectively with speakers from different cultures. Literary texts are full of cultural topics that can trigger learners’ comparison and contrast skills. Unfortunately, not many English textbook designers and language teachers are interested in using literature to teach English despite the richness in content, language use, idiom, and vocabulary. Following (Byram, 1997), this research endeavours to explore the relevance of using literature on EFL classrooms to develop learners’ intercultural communicative competence through an experiment done with a group of Moroccan high school learners. A survey developed by (Duisembekova, 2021) was adapted to collect data which was analyzed using (SPSS, edition 26). The study revealed that most learners exhibit positive attitudes and great motivation towards reading literary texts and discussing intercultural themes. It also demonstrated that a respectable number of learners have enhanced their analysis, interpretation and critical thinking skills. The results can serve as an incentive for educators and syllabus designers to rethink ways to appropriately incorporate literature within EFL classrooms.